Codigestion of food waste and real traditional Chinese medicine wastewater in anaerobic membrane bioreactor: Stability mechanism and microbial community dynamics - Yong-Xin Cui; Bao-Shan Xing; Su Li; Zi-Yi Wang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Magnetic biochar as dual-functional mediator for low-field magnetic separation of vivianite and membrane fouling mitigation in anaerobic membrane bioreactors - Feng-Ai Yang; Ying Dong; Jifei Chang; Rong Chen; Xin Wang; Juncheng Liu; Fernanda Leite Lobo; Devard I. Stom; Nan Li (Bioresource Technology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

Regulating proton back-diffusion to enhance lithium sulfate conversion in bipolar membrane electrodialysis - Rong Zhang; Lingyun Wang; Xin Wang; Zhe Yu; Wenkai Wang; Ming Tan; Yang Liu; Yang Zhang (Desalination, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Integrated network toxicology, transcriptomics, and metabolomics revealed the potential mechanisms of aluminum-induced testicular injury - Siyu Liao; Liqing Huang; Yusi Zhou; Xin Zhang; Shaofeng Huang; Linjun Yu; Shiman Zhu; Wei Chen; Rong Wang; Haimei Qin (Food and Chemical Toxicology, 2026)

Advanced nitrogen removal system coupling partial nitritation, anammox, denitrification and oxygen-permeable hollow-fibre membranes for precise oxygen regulation - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Liguo Wan; Ling-Hu Li; Xin-Xin Sun; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

A robot herding strategy combining CMFF and MPC for shepherding - Hongbo Liu; Ping Song; Gang Liu; Xiaoping Xin; Yuping Rong; Luyu Ding; Junyao Gao; Zhuoming Wang; Yinglong Zhang; Pengzhen Li (Computers and Electronics in Agriculture, 2026)

Characterization of CYP402C5 associated with field resistance to three neonicotinoids in Bemisia tabaci - Chao Wang; Rong Zhang; Jing Yang; Mingjiao Huang; Hantang Lu; Ying Zhang; Youjun Zhang; Junkai Li; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Continuous coagulant and alkali dosing enhanced organic separation from hypersaline wastewater in synchronous ozonation coagulation process - Yuhan Yang; Mengwen Liu; Rong Liu; Yiqiao Shi; Yadong Wang; Yukai Zong; Zimin Lu; Xu Lu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

pH-responsive, self-lubricating hyaluronic acid-chondroitin sulfate-chitosan hydrogel for articular cartilage repair - Haofeng Qiu; Jingfang Zheng; Zheyu Yao; Ximing Cai; Gaoke Pan; Xufeng Mao; Xin Zhao; Lei Shao; Dangsheng Xiong; Rong Wang; Yi Zhang (Carbohydrate Polymers, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Exploring root-mediated Erwinia amylovora invasion mechanism in Korla fragrant pear (Pyrus sinkiangensis) - Lili Han; Yue Sun; Xin Deng; Jiehua Wang; Feng Zhang; Weimin Chen; Rong Lei (European Journal of Plant Pathology, 2026)

Impacts of trunk height, tree planting density, and wall heating on flow and pollutant dispersion inside an urban street canyon - Yuan-Dong Huang; Yan-Jiao Jiang; Rong Ji; Ke-Xin Wang; Meng-Xin Chai; Yang Luo; Peng-Yi Cui (Environmental Fluid Mechanics, 2026)

A Quad-Polarimetric SAR image reconstruction network and wetland classification fusing optical texture and polarization information - Yating Zhan; Yujun Wang; Ke Song; Yiming Su; Xin Rong; Gui Zhou; Yefei Zhu; Ziqiao Xu (International Journal of Remote Sensing, 2026)

Corridor-scale sea-ice navigability and its interannual volatility: a multi-model assessment of the Arctic Europe–Pacific route - Rong Wang; Jiabiao Li; Ni Feng; Yuyang Liang; Xin Zhou; Jian Ren; Zhixiong Yao (Frontiers in Marine Science, 2026)
Climate warming has brought encouraging prospects for Arctic shipping, with many studies projecting longer navigable seasons and expanded route availability as sea ice declines. Yet most assessments still focus on the lengthening of open-water duration, that is, mean accessibility, while giving less systematic attention to interannual volatility, a factor that fundamentally shapes commercial viability, insurance pricing, and long-term infrastructure investment. This is not simply an empirical omission but an integration gap: existing navigability assessments often operationalize accessibility through mean or threshold-based metrics, without treating year-to-year predictability as a distinct, governance-relevant dimension. Here we develop a corridor-scale, threshold-oriented framework that jointly evaluates navigability and its volatility, and we position this framework as a diagnostic instrument that helps translate climate variability into information usable for Arctic maritime governance. Focusing on an analysis corridor (30°E–170°W, 66–82°N) associated with Arctic Europe–Pacific connectivity, we analyze monthly sea-ice concentration from a five-model CMIP6 ensemble (MPI-ESM1-2-LR, ACCESS-CM2, CanESM5, MIROC6, and NorESM2-LM) under SSP2-4.5 and SSP5-8.5. Navigability is defined as months in which corridor-mean sea-ice concentration falls below 15%, and volatility is quantified as the 10-year centered rolling standard deviation of the annual open-water window; model biases are assessed against C3S satellite observations. Across both scenarios and consistently across models, the open-water window lengthens from the 2030s to the 2050s, increasing in the ensemble mean from about 2.6–2.9 to about 3.5–3.7 months yr - ¹. Volatility, however, does not decline in proportion, and its temporal structure is strongly scenario-dependent: under SSP5-8.5 it peaks in the first half of the century and then declines, whereas under SSP2-4.5 it remains persistently elevated through mid-century. The near-term 2035 planning window is nearly indistinguishable between scenarios, a result robust across SIC thresholds of 10–30%. In addition, corridor-mean navigability overestimates route-level navigability by 23–41%, with the Laptev Sea identified as the principal bottleneck. The framework provides a reproducible, volatility-aware basis for strategic risk stratification and contingency planning, distinguishing routes that are becoming more accessible from those becoming more predictable.

Overexpression of the MsCaM1 gene from alfalfa promoted growth and salinity tolerance in transgenic Arabidopsis - Rugang Yu; Xin Chen; Xinli Pan; Mengru Rong; Lin Yang; Guoliang Wang; Xueling Du (Journal of Plant Biochemistry and Biotechnology, 2026)

PM2.5 exposure exacerbates cerebral infarction via HPG axis downregulation and pituitary lipid metabolism dysregulation in mice - Xin lv; Guanhui Pei; Lijuan Liu; Zhou zhou; Yicong Zhou; Binbin Wang; Chaoyue Meng; Ruomeng Chen; Qiang Yao; Ge Bai; Xuelin Wang; Minghan Zhao; et al. (NeuroToxicology, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Integrating environmental DNA and trawl surveys to assess seasonal dynamics of fish communities in the Oujiang River Estuary - Chen Weifeng; Ruan Huiting; Wang Wei; Xu Kaiping; Peng Xin; Zhu Rong; Lu Yumiao; Ye Shen; Lin Hungdu; Wang Chen; Zhou Xiaofeng (Frontiers in Marine Science, 2026)
Introduction Monitoring of estuarine fish biodiversity is often constrained by the inherent limitations of traditional survey methods and the complex, dynamic environmental conditions of estuarine habitats. Environmental DNA (eDNA) metabarcoding has emerged as a robust molecular tool for aquatic biodiversity assessment. Nevertheless, its complementary potential to conventional bottom trawling remains understudied in estuarine ecosystems. In this study, we integrated eDNA metabarcoding and bottom trawling to investigate the spatiotemporal dynamics of fish diversity in the Oujiang River Estuary (ORE). Methods Fish assemblage data were collected seasonally across four sampling periods at five fixed sites within the ORE. MiFish-U primers targeting the 12S rRNA gene were utilized for eDNA amplification. And twelve aquatic environmental variables were quantified to disentangle correlations between fish community structure and ambient environmental conditions. Multiple statistical approaches, including alpha diversity analysis, Principal Coordinate Analysis (PCoA) and PERMANOVA, were applied to quantify spatiotemporal shifts in fish assemblages, identify fish-environment correlations, and compare community discrepancies between the two survey methods. Results and discussion The combined approach detected a total of 100 fish species across 84 genera and 45 families. Specifically, eDNA metabarcoding identified 72 fish species, while bottom trawling captured 48 species, with only 20 species shared between the two methods. Fish assemblages exhibited distinct seasonal variations, with both survey methods revealing higher species richness during wet seasons. Temporal fluctuations in water temperature, dissolved oxygen, salinity and nutrient concentrations constituted the primary environmental drivers structuring estuarine fish assemblages, whereas spatial heterogeneity across sampling sites exerted no statistically significant influence on community composition. eDNA metabarcoding showed unique advantages in detecting pelagic, migratory, cryptic and endangered fish species, supporting effective biodiversity monitoring in topographically intricate estuarine waters. In contrast, bottom trawling provided reliable morphological identification and quantitative abundance data for demersal fish taxa, which helped resolve ambiguous species annotations derived from eDNA sequencing. In addition, seven IUCN-listed threatened fish species were documented during the field investigation. Collectively, our findings demonstrate that eDNA metabarcoding and bottom trawling serve as highly complementary, rather than mutually exclusive, tools for fish biodiversity assessment. The integration of the two methods enables a more comprehensive and accurate evaluation of estuarine fish diversity. This study validates the feasibility and efficacy of the combined monitoring framework for macrotidal estuaries and provides valuable scientific references for the ecological conservation and management of the Oujiang River Estuary as well as other similar coastal ecosystems.

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Mineralogical tracers for magmatic and hydrothermal controls on Nb-Ta-Li mineralization: a case study from the Hailuoling granite system, Southern China - Qifei Shi; Bin Wu; Xin Gui; Qian Ren; Guanglai Li; Rong Yin; Qingfei Wang (Mineralium Deposita, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Biological characterization of an avian leukosis virus subgroup J isolate from yunnan indigenous black-bone chickens and generation of its full-length infectious clone - Hongya Yan; Guojun Wang; Rong Zhao; Ke Li; Zhengju Yuan; Wengui Li; Aiguo Xin (Archives of Virology, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Synergistic antifouling and organic removal using Fe/N co-doped biochar-modified ceramic membranes via in situ peroxymonosulfate activation - Rong Liu; Ye Zhu; Peng Ren; Jinge Fan; Yadong Wang; Mengwen Liu; Yabo Shang; Lu Xu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Chemical Engineering Journal, 2026)

Fe-regulated AnMBR for carbon & phosphorus co-recovery and membrane fouling control - Ying Dong; Rong Chen; Jifei Chang; Fengai Yang; Zhen Lei; Xin Wang; Nan Li (Chemical Engineering Journal, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Rapid retreat of the East Asian summer monsoon at the end of the Holocene humid period accelerated the transition from broadleaf to pine forest landscapes in northern China - Linjing Liu; Xin Mao; Lei Song; Xingqi Liu; Dejun Wan; Gaolei Jiang; Jingsong Yang; Hongmei Zhao; Chengmin Wang; Hua Zhao; Rong Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Apportioning nitrate sources via dual isotope, PMF and SIAR in a complex urban river network during flood season: Implications for engineered mitigation strategies - Xin Wang; Qiaoyun Lin; Zhixiong Huang; Yihua Cai; Wenjing Wang; Nan Rong; Siye Wei; Renren Wu; Quan Zhou (Journal of Water Process Engineering, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Antibacterial mechanism of Sanguinarine against Klebsiella pneumoniae and its efficacy in reducing bacterial contamination in milk - Ruiying Wang; Diangang Han; Tianlong Hu; Rong Zhao; Yanlin Li; Qiqi Pu; Ju Zeng; Xiong Dai; Long Zhang; Jige Xin (Food Bioscience, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

Efficacy and Safety of Temozolomide for the Treatment of Advanced or Recurrent Ependymoma: A Meta-Analysis - Rong Zhang; Binyan Liu; Zhuang Kang; Shenglan Li; Yingfan Sun; Jiachen Wang; Xin Yang; Shuo Yin; Feng Chen; Wenbin Li (Journal of Pharmaceutical Innovation, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

A scalable human liver-on-a-chip platform for predictive safety assessment - Gauri Kulkarni; Lizao Chen; Jing Sang; Ji Hye Seo; Romain Grall; Yunfang Wang; Paige Gilbride; Yu-Chieh Yuan; Matthew Albaum-Getzen; Jenna McCormack; Jingzhe Ma; Alyssa Fanelli; et al. (Toxicology, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Metabolic engineering of Pichia pastoris for high-efficiency production of branched-chain amino acids -enriched single-cell protein - Cancan Dong; Kai Hong; Fan Wu; Yanfeng Wang; Youyan Rong; Xin Wu; Jian Zhang; Le Gao (Bioresource Technology, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Low-δ18O magmas at Batur, Indonesia: Evidence for slab-window melting beneath arc volcanoes - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2026)

Robust copper/mesoporous silica catalyst for efficient furfural hydrogenation to furfuryl alcohol - Xin-Yu Xiao; Jie Zhang; Rong Wang; Qi Wang; Hai-Song Li; Jing-He Yang (Biomass and Bioenergy, 2026)

Asymmetric responses of above- and below-ground traits to light and nitrogen stress in three vegetable types - Rong Liang; Ruifang Zhang; Chi Zhang; Hong Wang; Xin-Xin Wang (Plant and Soil, 2026)

Assessing the impact of the Lahaina Maui wildfire on chemical and microbiological quality of coastal beach water - Yangyang Zou; Min Ki Jeon; Xin Wang; Mandy-Tanita Brinkmann; Kexin Rong; Xiaolong Geng; Tao Yan (Environmental Monitoring and Assessment, 2026)

Electrohydrodynamic (EHD) drying of Polygonatum sibiricum: Kinetics, physicochemical quality, and energy efficiency analysis - Xin Li; Yunfeng Wang; Ming Li; Phavady Phoodthahaksa; Jiangtao Rong; Huai Chen; Qingyun Li; Xueping Tang; Min Xu; Tarek Kh Abdelkader (Journal of Stored Products Research, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Targeted interception of membrane foulants in MBR: A straw-microplastic composite adsorbent for effective removal of oil and biopolymeric contaminants from catering wastewater - Rong Zhang; Beiyu Xin; Cong Zhang; Xiaozheng Ma; Ruoxin Wang; Jifeng Guo (Journal of Hazardous Materials, 2026)

Identification of a novel selenium peptide from Oryzain α hydrolysate: Selenium-specific database establishment, sequence confirmation, and molecular interaction analysis - Xin Wang; Bailiang Xue; Rong Zhang; Lin Shi; Wei Jia (Food Bioscience, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Revealing the role of spin state in catalysis: Medium spin Fe3+ catalyst for lithium‑sulfur batteries - Xin Dong; Rong Yang; Xifei Li; Peiying Li; Yurou Wang; Xuchen Li; Hongyu Shang; Jiaze Li; Chaojiang Fan; Yinglin Yan; Yunhua Xu (Chemical Engineering Journal, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Defect structures of mineral surface and its influence on flotation: a critical review - Chenyang Zhang; Minsheng Fu; Xin Rao; Rong Wang; Zhipeng Tang; Sun Wei (Minerals Engineering, 2025)

Field verification of the surface renewal method for evapotranspiration measurement in arid agricultural area: The uncertainty of calibration parameter - Zhen Wang; Nanjuan Zheng; Bingbing Jiang; Yao Rong; Xin Li; Peijin Wu; Weishu Wang; Chenglong Zhang; Zailin Huo (Journal of Hydrology, 2025)

Reversing the paradigm: Oxygen-dependent switch of nTiO₂ from promoting to suppressing ARG conjugation - Jie Yu; Xin Wang; Ya-Xin Hu; Feng-Ting Cao; Qiu-Rong Zhang; Xiang-Tong Zhou; Xiang Xiao (Journal of Hazardous Materials, 2025)

Fluvial response to differential activity of the Litang fault system: Implications for fault kinematics and geodynamics in the southeastern Tibetan Plateau - Jinhan Wang; Xuhua Shi; Rong Yang; Hanlin Chen; Huili Yang; Yuanhai Shu; Zhuona Bai; Chenchao Xu; Xin Liu (Geomorphology, 2025)

Adulteration of animal-derived whey protein in infant formula: High-throughput screening of characteristic peptides - Lin Shi; Wei Jia; Rong Zhang; Xin Wang; Haizhen Mo (Food Research International, 2025)

Short-term ozone exposure and schizophrenia hospitalization risk: temperature modifying effect and greenspace mitigating effect - Chuan Li; Xin Yu; Rong Song; Yanhong Fang; Jiayuan Yang; Zhiyuan Tang; Shaoqi Wang; Xunrong Cheng; Weizhuo Yi; Rubing Pan; Jian Song; Hong Su (Environmental Pollution, 2025)

Boron promoted Pt/Al2O3 catalysts with superior stability for Methylcyclohexane dehydrogenation - Voon Huey Lim; Hossein Akhoundzadeh; Zheng Wang; Shenghui Zhou; Chao Wu; Mohammadreza Kosari; Chi Cheng Chong; Xin Zhao; Shibo Xi; Rong Xu (Chemical Engineering Journal, 2025)

Carbonized polymer dots with conjugated core to induce dynamic interfacial protection layer formation for advanced zinc metal batteries - Jiayu Zhang; Wenchen Wang; Xiaoyan Shen; Yihan Song; Rong Li; Xin Ji; Xinyi Hu; Xiaoyu Deng; Haizhu Sun (Chemical Engineering Journal, 2025)

An injectable and programmable hydrogen delivery system for modulation tendon tissue in tendon-bone interface microenvironment - Tao Yuan; Fei Jin; Lili Qian; Xiaojiang Yang; Xin Yu; Zhongyang Lv; Ziying Sun; Shiwen Shen; Hong Qian; Jia Meng; Hui Jiang; Wenshuang Sun; et al. (Chemical Engineering Journal, 2025)

Adaptive responses of soil phosphorus availability and plant phosphorus resorption to nitrogen enrichment-induced phosphorus limitation in a boreal peatland - Yu-Xin Ji; Le-Lin Yu; Zhen Zeng; Xian-Wei Wang; Rong Mao (Plant and Soil, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

A strain of mycovirus AaVV1 mediates hypovirulence of Alternaria species - Ya Rong Wang; Yi Chen; Chang Xin Li; Xiao Gang Li; Jun Zi Zhu; Jie Zhong (Pesticide Biochemistry and Physiology, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

Orbital-engineering-enabled electrified ferrocene–FeOOH membrane for effective flow-through organoarsenic mineralization and arsenic sequestration - Xin Gao; Qian Li; Rong Chen; Xuefeng Liu; Lin Yang; Yongshen Hou; Hao Sun; Yanbiao Liu; Haitao Wang; Yi Wang (Chemical Engineering Journal, 2025)

Multi-scale piezoresistive foam composed of graphene skeleton and vertical WS2 nanosheets designed for wearable detection/protection applications - Tengyue Song; Minxuan Xu; Yueqin Shi; Xin Li; Hang Wang; Zhe Kong; Suyu Sheng; Qi Zhang; Rong Xiang (Chemical Engineering Journal, 2025)

Haloxylon ammodendron plantations: enhancing multi-trophic arthropod diversity and soil multifunctionality in arid deserts - Jialong Ren; Yongzhen Wang; Xiaogan Zhou; Wenzhi Zhao; Zhibin He; Rong Yang; Weidong Xin; Wei Ren; Chengchen Pan; Jiliang Liu (Journal of Environmental Management, 2025)

DPP-IV inhibitory peptides from highland barley via machine learning and multi-scale validation - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Rong Li; Kefan Wei; Jiaqian Cao; Qingyu Zhao; Qun Shen; Yong Xue (Food Chemistry, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Editorial for Special Issue: Sino-German P&RS Cooperation: Applications, Methods, Reviews - Xin Wang; Ludwig Hoegner; Rong Huang; Lei Ma; Yusheng Xu (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)

STL-GT: graph-structured learning based transformer for GNSS positioning enhancement in urban environments - Zhenni Li; Xin Li; Qianming Wang; Rong Yuan; Xuesong Tan; Maodeng Li; Marios M. Polycarpou; Shengli Xie (GPS Solutions, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

Synergistic antimicrobial effect and mechanism of enterocin Gr17 and cinnamaldehyde against Escherichia coli and Candida albicans - Wen-yu Ma; Kai-sheng Shen; Zhao Wang; Qi Liu; Xin-jie Diao; Guo-rong Liu (Archives of Microbiology, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Two new steroidal saponins from the roots and rhizomes of Helleborus thibetanus - Hao Wei; Xin Zhang; Chao Ding; Yuze Li; Ziqiang Wang; Xiaomei Song; Dongdong Zhang; Rong Lin (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

The first set of Silurian marine red beds in South China: Spatiotemporal distribution, diachronism and paleogeographic significance - Xiaole Zhang; Jiayu Rong; Peng Tang; Renbin Zhan; Yi Wang; Zhongyang Chen; Ruiwen Zong; Bing Huang; Xin Wei (Science China Earth Sciences, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Analysis of CO2 emission and energy consumption in CCUS for steel-chemical joint production - Huapeng Yang; Chao Feng; Tao Lin; Rong Zhu; Kai Dong; Guangsheng Wei; Mingwei Tu; Fuhai Liu; Ziheng Zhao; Xin Ren; Chunyang Wang (Journal of Environmental Management, 2025)

Bioturbation and the effects on benthic flux of nitrogen in a large eutrophic lake: Insights from 224Ra/228Th disequilibrium and inverse geochemical modelling - Xiaoyan Shi; Guodong Chen; Rong Mao; Xin Luo; Jiu Jimmy Jiao; Meiqing Lu; Tianwei Wang; Wenli Hu; Xingxing Kuang (Geochimica et Cosmochimica Acta, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Explicit backbone curve prediction of corroded reinforced concrete columns using simulated annealing-optimized genetic programming - Le-Rong Wang; Qing-Feng Liu; Bo Wu; Xin-Yu Zhao (Engineering Structures, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Fine mapping and functional validation reveal two incomplete dominant genes controlling photoperiod-sensitive flowering in Gossypium hirsutum - Langjing Hua; Chao Xu; Xiao Liu; Zhicheng Wang; Tengyu Li; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Theoretical and Applied Genetics, 2025)

Partitioning of evapotranspiration in semi-arid rain-fed farmland using an improved stomatal conductance model - Yongzhi Bao; Tingxi Liu; Limin Duan; Xin Tong; Yixuan Wang; Lina Hao; Rong Hua; V. P. Singh (Irrigation Science, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

A critical review on pear Fruit’s polyphenols and its chlorogenic acid: Composition, bioavailability, and pharmacological potential - Abdul Basit; Raheem Shahzad; Abdul Mueed; Asim Muhammad; Wang Rong; Liu Ya; Gong Xin; Khanizadeh Shahrokh; Muhammad Arshad; Tao Shutian (Food Bioscience, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Genomic and antimicrobial resistance profiles of Clostridium perfringens isolated from pets in China - Mingjin Fang; Yuan Yuan; Xin Tian; Ying Liu; Ke Wu; Yanyan Zhu; Likun Zhang; Edward M. Fox; Ruichao Li; Li Bai; Menghan Li; Guerrino Macori; et al. (Veterinary Microbiology, 2025)

Development of a novel fluorescent probe for the detection of glyphosate in food and water samples and the construction of a smartphone-assisted platform - Xiaodi Rong; Caiyun Liu; Fengli Hou; Xin Zhao; Zhongpeng Wang; Baocun Zhu (Food Chemistry, 2025)

Identification of the chemical composition of blue honeyberry leaves (Lonicera caerulea L. var. edulis) and their anti-inflammatory activity - Zhenji Rong; Chunping Yu; Xin Wang; Ruyue Wang; Yang Gao; Hailong Zhang (Medicinal Chemistry Research, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

Design, synthesis, biological evaluation, and in silico studies of imidazo[2,1-b][1,3,4]thiadiazole derivatives as cholinesterase inhibitors - Wen-Rong Du; Yi-Xuan Wang; Xue-Wei Zhou; Yong Lan; Ben-Ben Wei; Xin-Yuan Guo; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2025)

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Petrogenesis and geodynamic implications of gabbroic diorites of the early Paleozoic Mijiashan ophiolite in the eastern North Qilian Orogenic Belt, NW China - Jiao-Long Zhao; Liang Liu; Qing-Yan Tang; Jin-Rong Wang; Zhen-Xi Yang; Pei-Qing Hu; Xin-Wei Zhai; Saniye Abdereyimu; Zi-Han Dang (Journal of Asian Earth Sciences, 2025)

Nonradicals-dominated peroxymonosulfate activation of g-C3N4/CeO2 floating beads for enhanced inactivation of M. aeruginosa: Performance studies and mechanistic insights - Dandan Wang; Jing Li; Rong Zhang; Beiyu Xin; Xueru Huang; Yang Wang; Jifeng Guo (Chemical Engineering Journal, 2025)

Seasonal variations in the soil microbiota of a temperate wetland in Northeast China in response to nitrogen deposition - Rong-Tao Zhang; Shen-Zheng Wang; Hai-Xiu Zhong; Xin Sui; Ying-Nan Liu (CATENA, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

Data-driven optimization reveals the impact of Urban Heat Island effect on the retrofit potential of building envelopes - Renge Li; Chenyu Huang; Weilin Xin; Jiahong Ye; Xue Zhang; Rong Qu; Jinyu Wang; Liang Yuan; Jiawei Yao (Building and Environment, 2025)

Model-based analysis for investigating the impact of tumor size, lymphocyte and neutrophil on the survival of breast cancer 4T1 tumor-bearing mice - Qing-yu Yao; Xin-yu Hou; Wei-zhe Jian; Tian-yu Wang; Ping-yao Luo; Jun-sheng Xue; Rong Chen; Tian-yan Zhou (Toxicology and Applied Pharmacology, 2025)

Occurrence characteristics and factors that influence shale oil in the Jurassic Lianggaoshan Formation, northeastern Sichuan Basin - Xuefeng Bai; Xin Wang; Min Wang; Junhui Li; Shuangfang Lu; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Youzhi Wang (Marine and Petroleum Geology, 2025)

Electromagnetic field coupled vertical flow constructed wetlands for rural sewage treatment: Performance, microbial community characteristics and metabolic pathways - Xiuxiu Lu; Yan Wang; Yungen Liu; Xin Xue; Chuandong Fu; Liechao Xiong; Liping Peng; Silin Yang; Rong Ma (Journal of Environmental Management, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Nickel-iron layered double hydroxide and CoMoO4 composites supported on nickel foam as efficient bifunctional catalyst for water electrolysis - Xin Xiao; Rao Ma; Ke Jiang; Lushan Ma; Qiyao Wang; Shuang Meng; Tong Yang; Zhuo Qiu; Rong Hu; Long Huang (Fuel, 2025)

Prevalence and genomic characteristics of becAB-carrying Clostridium perfringens strains - Mingjin Fang; Yuan Yuan; Edward M. Fox; Ke Wu; Xin Tian; Likun Zhang; Hang Feng; Ruichao Li; Li Bai; Xinglong Wang; Zengqi Yang; Rong Zhang; et al. (Food Microbiology, 2025)

MOFs meets wood: Renewable, self-supporting carbon-based composites for electromagnetic interference shielding with heat-resistant and electrothermal management - Yujun Rong; Xin Zhou; Shaohua Jiang; Wenkai Zhu; Hanwei Wang; Baokang Dang; Qingfeng Sun; Xiaofan Ma (Chemical Engineering Journal, 2025)

A novel measurement for evaluating the capture efficiency of local ventilation system using background oriented schlieren - Junhao Rong; Yanqiu Huang; Yihang Zhao; Yi Wang; Xin Li; Junwei Guo; Wenyang Wang; Shengnan Guo (Building and Environment, 2025)

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Coupling polyethylene microplastics with other pollutants: Exploring their combined effects on plant health and technologies for mitigating toxicity - Linmei Cui; Rong Liang; Chi Zhang; Ruifang Zhang; Hong Wang; Xin-Xin Wang (Science of The Total Environment, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Microscopic mechanisms and durability evaluation under freeze-thaw conditions of heavy metal solidification in red mud-slag geopolymer - Lu Zhou; Xin Xu; Qing Wang; Junboum Park; Yongming Han; Lisheng Guo; Rong Chen (Journal of Environmental Chemical Engineering, 2024)

Investigation of the intelligent anti-aging bitumen using microcapsule clean-product secreting waste cooking oil through polyacrylamide-gel in porous-shell structure - Qian Sun; Qin-Yu Xing; Rong-Yue Shao; Jun-Feng Su; Xin-Yu Wang (Fuel, 2024)

Effects of different fermentation modes on tea leaves: Revealing the metabolites modification by quasi-targeted metabolomics - Xin Fang; Rong Xue; Jingyi Xiao; Qian Pu; Yufei Wang; Yuan Yuan; Bin Liu; Mengyuan Sui; Guangxian Jiang; Rida Niaz; Yongping Sun; Ziming Yu; et al. (Food Bioscience, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Performance of a novel annular electric field membrane bioreactor and its membrane fouling control in treating catering wastewater - Rong Zhang; Mengqian Li; Huan Ma; Yanyan Wang; Beiyu Xin; Jifeng Guo (Chemosphere, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Study on Translational toxicology of Senna obtusifolia aqueous extract - Xin Guo; Liping Gong; Chong Guo; Taotao Cai; Nana Huang; Xianhui Shen; Lisong Sheng; Rongrong Li; Yanqing Wang; Xinmei Zhao; Wenhe Guo; Rong Sun (Toxicon, 2024)

Quantitative evaluation of hydrate-based CO2 storage in unsealed marine sediments: Viewpoint from the driving force of hydrate formation and CO2-water contact ability - Hong-Nan Chen; Yi-Fei Sun; Wei-Xin Pang; Ming-Long Wang; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Bo-Jian Cao; Dan Rao; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2024)

Improving curcumin bioavailability: Targeted delivery of curcumin and loading systems in intestinal inflammation - Junyi Zhao; Wei Jia; Rong Zhang; Xin Wang; Li Zhang (Food Research International, 2024)

Investigation of isomerization and oxidation of astaxanthin in ready-to-eat Litopenaeus vannamei during accelerated storage - Na Li; Xin Fan; Yefan Wang; Kexin Zhang; Rong Liu; Yunpeng Xu; Zhifeng Tan; Wensi Xu; Dayong Zhou; Deyang Li (Food Research International, 2024)

Dynamic changes in the aroma profiles and volatiles of Enshi Yulu tea throughout its industrial processing - Guangxian Jiang; Rong Xue; Jun Xiang; Yufei Wang; Bin Liu; Yuan Yuan; Qian Pu; Xin Fang; Xingming Hu; Xiaoying Liu; Youyi Huang (Food Chemistry, 2024)

Impacts of nano- and micro-plastics exposure on zooplankton grazing, bacterial communities, and dimethylated sulfur compounds production in the microcosms - Yu Jiang; Juan Yu; Rong Chen; Su Wang; Gui-Peng Yang; Long-Fei Liu; Xin-Ran Song (Environmental Pollution, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Effects of microplastics derived from biodegradable mulch film on different plant species growth and soil properties - Rong Liang; Chi Zhang; Ruifang Zhang; Qingyun Li; Hongquan Liu; Xin-Xin Wang (Science of The Total Environment, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Late cretaceous intraplate magmatism in Central and South Pamir: Response to edge-driven convection - Xin Ma; Jian Wang; Wei Dan; Qiang Wang; Guo-Rong Tang; Mustafo Gadoev; Ilhomjon Oimahmadov; Murodov Azamdzhon; Sharifjon Odinaev; Gong-Jian Tang (Lithos, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Design, synthesis and evaluation of imidazo[1,2-a]pyrazin-8(7H)-one derivatives as acetylcholinesterase inhibitors and antioxidants - Wen-Rong Du; Ben-Ben Wei; Xin-Yuan Guo; Yong Lan; Pan-Pan Shang; Yi-Xuan Wang; Xue-Wei Zhou; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

The effects of diverse microplastics on adzuki bean (Vigna angularis) growth and physiologic properties - Rong Liang; Feihu Sun; Xiaomei Yang; Hongquan Liu; Xin-Xin Wang (Environmental Geochemistry and Health, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

Structured carbon for electromagnetic shielding and microwave absorption from carbonization of waste Polymer: A review - Jiang-Tao Liu; Yu-Chen Zheng; Xin Hou; Xue-Rong Feng; Ke Jiang; Ming Wang (Chemical Engineering Journal, 2024)

Arc building and maturation of the Lombok Island, East Sunda Arc - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Yun-Ying Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Utilization of tofu wastewater and Nannochloropsis oceanica for eutrophication mitigation and eicosapentaenoic acid valorization: Advancing carbon neutrality and resource recycling - Yuqin Li; Xing Meng; Zhenyao Wang; Xin Lin; Yuan Xu; Jinhua Mou; Rong Zhou; Yufang Tang; Carol Sze Ki Lin; Xuan Li (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Deubiquitinating enzyme OTUD4 stabilizes RBM47 to induce ATF3 transcription: a novel mechanism underlying the restrained malignant properties of ccRCC cells - Ziyao Li; Ye Tian; Huafeng Zong; Xuelei Wang; Dongyang Li; Adili Keranmu; Shiyong Xin; Bowen Ye; Rong Bai; Weihua Chen; Guosheng Yang; Lin Ye; et al. (Apoptosis, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Toxic nonpreferred species accelerate the natural restoration of plant productivity and diversity in degraded grasslands - Xiaona Zheng; Chen Chen; Xin Dai; Le Lang; Xing Li; Jigui Chen; Rong Wang; Wenhui Cai; Ying Gao (Science of The Total Environment, 2024)

Novel insights into dimethylsulfoniopropionate cleavage by deep subseafloor fungi - Xuan Liu; Xin-Ran Wang; Fan Zhou; Ya-Rong Xue; Xiang-Yang Yu; Chang-Hong Liu (Science of The Total Environment, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Water-soluble metal-organic cages crosslinked injectable hydrogel for multi-modal synergistic therapy - Wen-Zhen Li; Xiao-Fan Rong; Yu Wang; Jia-Wen Xiong; Na Zhou; Zi-Xin Wang; Xi-Jia Fang; Wenjing Wang; Yi Liu; Xiao-Qiang Wang (Chemical Engineering Journal, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Glutathione S-transferase directly metabolizes imidacloprid in the whitefly, Bemisia tabaci - Rong Zhang; Jing Yang; Jinyu Hu; Fengbo Yang; Jinjin Liang; Hu Xue; Xuegao Wei; Buli Fu; Mingjiao Huang; He Du; Chao Wang; Qi Su; et al. (Pesticide Biochemistry and Physiology, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Building a stable and robust anti-interference DNA dissipation system by eliminating the accumulation of systemic specified errors - Luojia Wang; Wang Luo; Zhi Weng; Zhongzhong Wang; You Wu; Rong Zhao; Xiaole Han; Xin Liu; Jianhong Zhang; Yujun Yang; Guoming Xie (Analytica Chimica Acta, 2024)

Unearthing the soil‐borne microbiome of land plants - Raúl Ochoa‐Hueso; David J. Eldridge; Miguel Berdugo; Pankaj Trivedi; Blessing Sokoya; Concha Cano‐Díaz; Sebastian Abades; Fernando Alfaro; Adebola R. Bamigboye; Felipe Bastida; José L. Blanco‐Pastor; Asunción de los Rios; et al. (Global Change Biology, 2024)
Plant–soil biodiversity interactions are fundamental for the functioning of terrestrial ecosystems. Yet, the existence of a set of globally distributed topsoil microbial and small invertebrate organisms consistently associated with land plants (i.e., their consistent soil‐borne microbiome), together with the environmental preferences and functional capabilities of these organisms, remains unknown. We conducted a standardized field survey under 150 species of land plants, including 58 species of bryophytes and 92 of vascular plants, across 124 locations from all continents. We found that, despite the immense biodiversity of soil organisms, the land plants evaluated only shared a small fraction (less than 1%) of all microbial and invertebrate taxa that were present across contrasting climatic and soil conditions and vegetation types. These consistent taxa were dominated by generalist decomposers and phagotrophs and their presence was positively correlated with the abundance of functional genes linked to mineralization. Finally, we showed that crossing environmental thresholds in aridity (aridity index of 0.65, i.e., the transition from mesic to dry ecosystems), soil pH (5.5; i.e., the transition from acidic to strongly acidic soils), and carbon (less than 2%, the lower limit of fertile soils) can result in drastic disruptions in the associations between land plants and soil organisms, with potential implications for the delivery of soil ecosystem processes under ongoing global environmental change.

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

In-situ GSH-responsive gas nanogenerator for active NIR-II FL/PA imaging and synergistic restoration the macrophage niche in rheumatoid arthritis - Xiaochun Zheng; Weiwei Kang; Yarong Jin; Xin Zhang; Wenxuan Wang; Dongsheng Li; Shutong Wu; Lin Chen; Shichao Meng; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Mulch film to plastic debris: A survey of agricultural soils of Hebei Province, North China - Rong Liang; Zhejiang Zhu; Cong Peng; Zijia Bian; Xiaomei Yang; Hong Wang; Xin-Xin Wang (Science of The Total Environment, 2024)

Reservoir characteristics and controlling factors of the middle–high maturity multiple lithofacies reservoirs of the Lianggaoshan Formation shale strata in the northeastern Sichuan basin, China - Xin Wang; Min Wang; Chen Zhao; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Xinbin Zhao; Yulong Tang (Marine and Petroleum Geology, 2024)

Kinetics of fe-containing solid waste reduction by carbonaceous materials in CO2 atmosphere: The cause of reducing agent burnout during direct reduction treatment - Xin Li; Guangsheng Wei; Hongyang Wang; Bohan Tian; Rong Zhu; Yefeng Wang (Fuel, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Novel Pharmaceutical Cocrystals of Tegafur: Synthesis, Performance, and Theoretical Studies - Haoran Mei; Na Wang; Di Wu; Qi Rong; Xue Bai; Xin Huang; Lina Zhou; Ting Wang; Hongxun Hao (Pharmaceutical Research, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Chronic Pb exposure impairs learning and memory abilities by inhibiting excitatory projection neuro-circuit of the hippocampus in mice - Rong-Xin Zou; Xiaozhen Gu; Chenqing Huang; Hui-Li Wang; Xiang-tao Chen (Toxicology, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Steam disinfection enhances bioaccessibility of metallic nanoparticles in nano-enabled silicone-rubber baby bottle teats, pacifiers, and teethers - Yu Su; Bin Wang; Xin Tong; Shuchuan Peng; Sijin Liu; Baoshan Xing; Rong Ji (Journal of Environmental Sciences, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Interplanting leguminous shrubs boosts the trophic interactions of soil micro-food web in a karst grassland - Jiachen Wang; Jie Zhao; Rong Yang; Xin Liu; Xuyuan Zhang; Wei Zhang; Xiaoyong Chen; Wende Yan; Kelin Wang (Soil Biology and Biochemistry, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Stochastic and deterministic assembly processes of bacterial communities in different soil aggregates - Yan Wang; Kun Zhu; Xin Chen; Keyu Wei; Rong Wu; Gang Wang (Applied Soil Ecology, 2024)

An independent framework-based evapotranspiration model (IFEM) for dual-source: From field to regional scale - Shuai Wang; Chaozi Wang; Chenglong Zhang; Weishu Wang; Pu Wang; Xin Zhang; Xingwang Wang; Yao Rong; Di Wang; Guanhua Huang; Zailin Huo (Remote Sensing of Environment, 2023)

Echinacoside, a promising sortase A inhibitor, combined with vancomycin against murine models of MRSA-induced pneumonia - Tao Jiang; Dai Yuan; Rong Wang; Chunhui Zhao; Yangming Xu; Yinghui Liu; Wu Song; Xin Su; Bingmei Wang (Medical Microbiology and Immunology, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Determination and petroleum geochemical significance of short-chain alkylbenzenes in lacustrine source rocks - Zhao-Wen Zhan; Guo-Xiang Wang; Yankuan Tian; Xin Zhan; Tian Liang; Yao-Ping Wang; Yan-Rong Zou; Ping'an Peng (Organic Geochemistry, 2023)

Nanoscale evidence of zircon-coffinite-xenotime solid solution observed by atom probe tomography - Wenhao Zhao; Bi-Wen Wang; Li-Xin Gu; Xu Tang; Yu Liu; Muhammad Awais; Xiao-Chi Liu; Xian-Hua Li; Rong Hu; Qiu-Li Li (Chemical Geology, 2023)

Multifunctional dumbbell probes-based logic circuits: microRNAs logic detection and tumor cells identification - Xin Liu; Baiying Li; Qian Liu; Li Zhang; Rong Zhao; Di Wu; Luojia Wang; Zhongzhong Wang; Guoming Xie; Wenli Feng (Analytica Chimica Acta, 2023)

N, N-bis (2-hydroxyethyl) malonamide based amidoxime functionalized polymer immobilized in biomembranes for highly selective adsorption of uranium(VI) - Yang Li; Ze-Yang Wang; Qi Ren; Feng Zhang; Xu-Xin Li; Qiang Wu; Rong Hua; Ze-Yi Yan; Yun Wang (Chemosphere, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Cretaceous magmatic migration and flare-up in Pamir–Karakoram - Xin Ma; Wei Dan; Jian Wang; Qiang Wang; Guo-Rong Tang; Mustafo Gadoev; Ilhomjon Oimahmadov; Gong-Jian Tang (Lithos, 2023)

In-situ constructing amidoxime groups on metal-free g-C3N4 to enhance chemisorption, light absorption, and carrier separation for efficient photo-assisted uranium(VI) extraction - Kaifu Yu; Yi Li; Xin Cao; Ruixiang Wang; Li Zhou; Linzhen Wu; Ningning He; Jia Lei; Dengjiang Fu; Tao Chen; Rong He; Wenkun Zhu (Journal of Hazardous Materials, 2023)

Application of super-cooled storage of aquatic products: A review - Xin-Yu Liu; Xue-Lai Zhang; Guan-Bang Wang; Fan-Yang Mo; Xin-Rong Zhang (International Journal of Refrigeration, 2023)

Control of hydrologic conditions and vegetation composition on carbon dynamics characterized by 13C enrichment in a dune-meadow cascade ecosystem in a semi-arid region - Xueer Kang; Tingxi Liu; Guanli Wang; Lina Hao; Limin Duan; Xin Tong; Vijay P. Singh; Rong Wu (CATENA, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The acceleration on decolorization of azo dyes by magnetic lignin-based materials via enhancing the extracellular electron transfer - Rong-ping Chen; Xin-yuan Wei; Cheng-hao Gan; Bing-cai Cai; Wen-jie Xu; Shareen Niyazi; Quan Wang; Lei Yu; Hui-hua Min; Qiang Yong (Journal of Environmental Management, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Prediction of daily PM2.5 and ozone based on high-density weather stations in China: Nonlinear effects of meteorology, human and ecosystem health risks - Lili Wang; Boya Liu; Rong Li; Xingfeng Chen; Lili Liu; Xiao Tang; Jingda Liu; Zhiheng Liao; Jinyuan Xin; Yuesi Wang; Bo Hu (Atmospheric Research, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Method for quantitative extraction of copper hydroxide nanoparticles from farmland soil - Xin-Yuan Li; Yuan Yang; Peng Huang; Ying-Rong Wang; Yu-Lin Nie; Li Zhang; Qiang Wang (Science of The Total Environment, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Dry-to-wet fluctuation of moisture contents enhanced the mineralization of chloramphenicol antibiotic - Shuhan Huang; Qilin Wang; Zhenhui Fan; Min Xu; Rong Ji; Xin Jin; Cheng Gu (Water Research, 2023)

Transformation of cognition from mechanical to biological aqueous outflow pump may be a breakthrough in solving the problem of intraocular pressure regulation in glaucoma - Shen Wu; Chen Xin; Wei Zhu; Yue Wan; Qing Sang; Rong Du; Jian Wu; Jin Wang; Ningli Wang (Science China Life Sciences, 2023)

Ectopic over-expression of HaFT-1, a 14-3-3 protein from Haloxylon ammodendron, enhances acquired thermotolerance in transgenic Arabidopsis - Rong Pan; Wenjing Ren; Shuanshuan Liu; Hua Zhang; Xin Deng; Bo Wang (Plant Molecular Biology, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

BPA exposure enhances the metastatic aggression of ovarian cancer through the ERα/AKT/mTOR/HIF-1α signaling axis - Xin Xie; Yan Zhu; Huimin Cheng; Haili Li; Yadi Zhang; Rong Wang; Wenyong Li; Fengrui Wu (Food and Chemical Toxicology, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Grass harvesting eliminates the beneficial effects of legume addition on soil nematode communities in a tall grass pasture - Jie Zhao; Wei Zhang; Xin Liu; Rong Yang; Dan Xiao; Xunyang He; Kelin Wang (Agriculture, Ecosystems & Environment, 2023)

Molecular detection and characterization of three novel parvoviruses belonging to two different subfamilies in zoo birds - Yan Wang; Yijie Sun; Xin Li; Rong Chen; Wang Li; Li Ji; Qifan Zhao; Likai Ji; Shixing Yang; Wen Zhang (Archives of Virology, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

The loss of Halloween gene function seriously affects the development and reproduction of Diaphorina citri (Hemiptera: Liviidae) and increases its susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Jing Wang; Tian-Rong Xin; Zhi-Wen Zou; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

Controllable Pd@Cu2O Schottky junction interface with improved anti-poisoning effect for efficiently electroreduction of CO2 into syngas - Rong Cai; Xin Du; Guorui Liu; Xiuli Wang; Qiang Tang; Xinpin Pan; Feng Li; Jing Li (Fuel, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Controllable acoustic deterrent based on the warning signals generated by nonel detonators - Long-Fei Huang; Xiao-Mei Xu; Yi Tao; Rong-Xin Wang; Yang-Liang Zhou; Fang-Gui Xiao (Marine Pollution Bulletin, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Ex vivo coronary endothelial cell activation associated with indoor coal combustion initiated atherosclerosis - Wanjun Zhang; Yaxian Pang; Wenting Cheng; Tao Wang; Yanting Li; Xin Li; Jianzhong Zhang; Xiaowen Xia; Yuxin Zheng; Rong Zhang; Jinglong Tang (Science of The Total Environment, 2023)

An antioxidant lignan glycoside and triterpenoid saponins from the leaves of Synsepalum dulcificum - Xin-Peng Li; Jun-Fei Wang; Rong Huang; Tang-Chang Xu; Si-Si Liu; Qing-Rong Yang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304 - Xin Qi; Wei-Hao Chen; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Yong-Hong Liu; Jun-Feng Wang; Yong Li (Natural Product Research, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Effects of substituting municipal waste incineration fly ash for lime on generating a bonding phase during the sintering process - Zhenqiang Jiang; Kai Dong; Hongyang Wang; Yun Zhou; Bohan Tian; Xin Li; Rong Zhu (Journal of Cleaner Production, 2023)

Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol - Ce Fu; Pan Wang; Rong-Hua Zhang; Luo-Yi Yan; Zheng Cheng; Xin Zhang; Xin-Wen Zhou (Fuel, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

QNE1 is a key flowering regulator determining the length of the vegetative period in soybean cultivars - Zhengjun Xia; Hong Zhai; Yanfeng Zhang; Yaying Wang; Lu Wang; Kun Xu; Hongyan Wu; Jinglong Zhu; Shuang Jiao; Zhao Wan; Xiaobin Zhu; Yi Gao; et al. (Science China Life Sciences, 2022)

Analysis of the effect of seasonal changes on sensitive parameters of LAI-based Penman–Monteith evapotranspiration model based on particle swarm algorithm - Hao Duan; Xin He; Hongli Zhao; Xiaohui Jin; Haowei Xu; Rong Wang (Acta Geophysica, 2022)

Characteristics of water vapor sources and precipitation contributions to drought and wet events on the Chinese Loess Plateau - Rong Liu; Xin Wang; Zuoliang Wang; Rui Quan (Theoretical and Applied Climatology, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Crustal Contamination of the Mantle-Derived Liuyuan Basalts: Implications for the Permian Evolution of the Southern Central Asian Orogenic Belt - Yuanyang Yu; Keqing Zong; Yu Yuan; Reiner Klemd; Xin-Shui Wang; Jingliang Guo; Rong Xu; Zhaochu Hu; Yongsheng Liu (Journal of Earth Science, 2022)

Microstructural Differences of the Cerebellum-Thalamus-Basal Ganglia-Limbic Cortex in Patients with Somatic Symptom Disorders: a Diffusion Kurtosis Imaging Study - Liao Dong; Huai-Bin Liang; Jiaxin Du; Yingying Wang; Qichen Zhou; Ziyue Xin; Yue Hu; Yi-Sheng Liu; Rong Zhao; Yuan Qiao; Chenglin Zhou; Jian-Ren Liu; et al. (The Cerebellum, 2022)

Atmospheric moisture sources of drought and wet events during 1979–2019 in the Three-River Source Region, Qinghai-Tibetan Plateau - Rong Liu; Xin Wang; Zuoliang Wang (Theoretical and Applied Climatology, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Case studies of atmospheric moisture sources in the source region of the Yellow River from a Lagrangian perspective - Rong Liu; Jun Wen; Xin Wang; Zuoliang Wang; Yu Liu (International Journal of Climatology, 2022)
In this study, atmospheric moisture source regions and transport pathways, which substantially affect extreme summer precipitation events in the source region of the Yellow River (SRYR) of China were investigated using the Lagrangian Flexible Particle Dispersion Model (FLEXPART). Based on the 24‐hour cumulative precipitation data from the China Meteorological Data Service Center, 2012 and 2015 were selected to represent wet and dry years during the period 2007–2016, respectively. The results indicate that potential moisture sources include the northern Tibetan Plateau, the Bay of Bengal, the southern edge of the Himalayas, Sichuan Basin, and the SRYR. In the wet year, moisture from the southern branch was transported along two pathways: (a) moisture from the Arabian Sea was carried by the Somalia jet and entered the SRYR through the Indian Peninsula and Bay of Bengal, and (b) moisture from the South China Sea entered the SRYR through the Sichuan Basin. In the dry year, the moisture primary originated from the northern branch. Moisture from the eastern European Plain or northern Africa was carried by the westerly jet and entered the SRYR. It is estimated that the ratios of moisture from the northern and southern branches contributing to the precipitation in the SRYR were 22.1 and 15.9% in the wet year, while they were 52.9 and 8.4% in the dry year, respectively. Internal moisture recycling contributed ~22.0% to precipitation in the wet year and 11.0% in the dry year. In this study, the transport trajectories of moisture contributing to extreme precipitation events in the SRYR are delineated. The results indicate that the northern branch is the primary contributor of moisture in the SRYR.

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Genetic diversity of Lathyrus sp collected from different geographical regions - Md. Mosiur Rahman; Md. Ruhul Quddus; Md. Omar Ali; Rong Liu; Mengwei Li; Xin Yan; Guan Li; Yishan Ji; Md. Monoar Hossain; Chenyu Wang; Ashutosh Sarker; Tao Yang; et al. (Molecular Biology Reports, 2022)

Caffeine Inhibits Activation of the NLRP3 Inflammasome via Autophagy to Attenuate Microglia-Mediated Neuroinflammation in Experimental Autoimmune Encephalomyelitis - Hui-Qi Wang; Kai-Yi Song; Jin-Zhou Feng; Si-Yuan Huang; Xiu-Ming Guo; Lei Zhang; Gang Zhang; Ying-Chao Huo; Rong-Rong Zhang; Yue Ma; Qing-Zhe Hu; Xin-Yue Qin (Journal of Molecular Neuroscience, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Source–sink dynamics assists the maintenance of a pollinating wasp - Xin Tong; Yuan‐Yuan Ding; Jun‐Yin Deng; Rong Wang; Xiao‐Yong Chen (Molecular Ecology, 2021)
Dispersal that unites spatially subdivided populations into a metapopulation with source–sink dynamics is crucial for species persistence in fragmented landscapes. Understanding such dynamics for pollinators is particularly urgent owing to the ongoing global pollination crisis. Here, we investigated the population structure and source–sink dynamics of a pollinating wasp ( Wiebesia sp. 3) of Ficus pumila in the Zhoushan Archipelago of China. We found significant asymmetry in the pairwise migrant numbers for 22 of 28 cases on the historical timescale, but only two on the contemporary timescale. Despite a small population size, the sole island not colonized by a superior competitor wasp ( Wiebesia sp. 1) consistently behaved as a net exporter of migrants, supplying large sinks. Comparable levels of genetic diversity, with few private alleles and low genetic differentiation (total F st : 0.03; pairwise F st : 0.0005–0.0791), were revealed among all the islands. There was a significant isolation‐by‐distance pattern caused mainly by migration between the competition‐free island and other islands, otherwise the pattern was negligible. The clustering analysis failed to detect multiple gene pools for the whole region. Thus, the sinks were most probably organized into a patchy population. Moreover, the estimates of effective population sizes were comparable between the two timescales. Thus the source–sink dynamics embedded within a well‐connected population network may allow Wiebesia sp. 3 to persist at a competitive disadvantage. This study provides evidence that metapopulations in the real world may be complicated and changeable over time, highlighting the necessity to study such metapopulations in detail.

Dual effects of insect fecundity overdispersion on the Wolbachia establishment and the implications for epidemic biocontrol - Xin Tong; Stephen G. Compton; Jing Jiao; Yan Chen; Yuan-Yuan Ding; Rong Wang; Xiao-Yong Chen (Journal of Pest Science, 2021)

Recombinant L-HN Fusion Antigen Derived from the L and HN Domains of Botulinum Neurotoxin B Stimulates a Protective Antibody Response Against Active Neurotoxin - Zhen Li; Jian-Sheng Lu; Shan Liu; Rong Wang; Qing Xu; Yun-Zhou Yu; Zhi-Xin Yang (Neurotoxicity Research, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Patterns of intrinsic brain activity in essential tremor with resting tremor and tremor-dominant Parkinson’s disease - Jun-ying Li; Zhong-jiao Lu; Xue-ling Suo; Nan-nan Li; Du Lei; Ling Wang; Jia-xin Peng; Li-ren Duan; Jing Xi; Yi Jiang; Qi-yong Gong; Rong Peng (Brain Imaging and Behavior, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Down-regulation of lncRNA CASC9 aggravates sepsis-induced acute lung injury by regulating miR-195-5p/PDK4 axis - Huai-rong Wang; Xiu-yan Guo; Xin-yan Liu; Xuan Song (Inflammation Research, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

Development and characterization of novel microsatellite markers in chestnut tiger butterfly Parantica sita (Lepidoptera: Nymphalidae) using next-generation sequencing - Ping Hu; Chia-Lung Huang; Min-Xin Luo; Yu-Feng Hsu; Rong-Jiang Wang (Applied Entomology and Zoology, 2020)

SsHKT1;1 is coordinated with SsSOS1 and SsNHX1 to regulate Na+ homeostasis in Suaeda salsa under saline conditions - Wen-Ying Wang; Ya-Qi Liu; Hui-Rong Duan; Xiu-Xia Yin; Yan-Nong Cui; Wei-Wei Chai; Xin Song; Timothy J. Flowers; Suo-Min Wang (Plant and Soil, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

Impact of calcium peroxide dosage on the control of nutrients release from sediment in the anoxic landscape water - Yi Wang; Wen-Huai Wang; Xin-Xin Lu; Lin-Lin Feng; Fu-Rong Xue; Lu-Qin Sun (Environmental Science and Pollution Research, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Convectively Coupled Equatorial Waves Simulated by CAMS-CSM - Lu Wang; Tianjun Zhou; Jian Li; Xinyao Rong; Haoming Chen; Yufei Xin; Jingzhi Su (Journal of Meteorological Research, 2019)

Relationship between genetic variation in the α2A-adrenergic receptor and the cardiovascular effects of dexmedetomidine in the Chinese Han population - Shao-jun Zhu; Kui-rong Wang; Xiong-xin Zhang; Sheng-mei Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

Arbuscular mycorrhizal fungi abundance was sensitive to nitrogen addition but diversity was sensitive to phosphorus addition in karst ecosystems - Dan Xiao; Rongxiao Che; Xin Liu; Yongjun Tan; Rong Yang; Wei Zhang; Xunyang He; Zhihong Xu; Kelin Wang (Biology and Fertility of Soils, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

A study of the characteristics of energy flux and its relationship with the summer monsoon over alpine wetlands in the source region of the Yellow River - Dongyu Jia; Jun Wen; Yaoming Ma; Juan Zhou; Jinlei Chen; Rong Liu; Xin Wang; Tangtang Zhang; Xin Lai; ZuoLiang Wang (Meteorology and Atmospheric Physics, 2019)

A B-box zinc finger protein, MdBBX10, enhanced salt and drought stresses tolerance in Arabidopsis - Xin Liu; Rong Li; Yaqing Dai; Li Yuan; Qinghua Sun; Shizhong Zhang; Xiaoyun Wang (Plant Molecular Biology, 2019)

Genomewide analysis of homeobox gene family in apple (Malus domestica Borkh.) and their response to abiotic stress - Rong Li; Hongjuan Ge; Yaqing Dai; Li Yuan; Xin Liu; Qinghua Sun; Xiaoyun Wang (Journal of Genetics, 2019)

Topical delivery of 3,5,4′-trimethoxy-trans-stilbene-loaded microemulsion-based hydrogel for the treatment of osteoarthritis in a rabbit model - Xiong-Bin Hu; Rong-Rong Kang; Tian-Tian Tang; Yong-Jiang Li; Jun-Yong Wu; Jie-Min Wang; Xin-Yi Liu; Da-Xiong Xiang (Drug Delivery and Translational Research, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

The warm season characteristics of the turbulence structure and transfer of turbulent kinetic energy over alpine wetlands at the source of the Yellow River - Dongyu Jia; Jun Wen; Yaoming Ma; Xin Wang; Tangtang Zhang; Rong Liu; Xin Lai (Meteorology and Atmospheric Physics, 2018)

Altered connectivity patterns among resting state networks in patients with ischemic white matter lesions - Ju-Rong Ding; Xin Ding; Bo Hua; Xingzhong Xiong; Yuqiao Wen; Zhongxiang Ding; Qingsong Wang; Paul Thompson (Brain Imaging and Behavior, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Late spring soil moisture variation over the Tibetan Plateau and its influences on the plateau summer monsoon - Juan Zhou; Jun Wen; Rong Liu; Xin Wang; Yan Xie (International Journal of Climatology, 2018)
Based on the European Centre for Medium‐Range Weather Forecasts (ECMWF) ERA‐Interim reanalysis data from 1979 to 2016, an index for Tibetan Plateau (TP) soil moisture ( I TPSM ), which could represent inter‐annual variation in spring soil moisture, is defined after removing the linear trend in soil moisture. The late spring soil moisture variation over the TP and its influences on the plateau summer monsoon are analysed. The results show that the TP soil moisture variation is non‐uniform, and spring soil moisture over the northeastern TP shows an increasing trend, while the western TP (especially the peripheral area) renders a significantly decreasing trend. When the I TPSM shows positive (negative) anomalies (i.e., spring soil moisture over the northeastern TP is higher (lower), soil moisture over the western TP is lower (higher) than normal), the plateau summer monsoon may be stronger (weaker). Anomalous variations in spring TP soil moisture can eventually affect the plateau summer monsoon by changing atmospheric circulation, diabatic heating, and water vapour transportation. It is found that when the I TPSM exhibits positive anomalies, diabatic heating over the centre and eastern TP is remarkably enhanced, and warm and humid moisture from the Bay of Bengal and Arabian Sea and cold air from high latitudes merge over the central and eastern TP; coupled with lower‐level convergence and upper‐level divergence, all these contribute to an increase in plateau summer monsoonal precipitation. When the I TPSM shows negative anomalies, diabatic heating over the centre and eastern TP is weakened, the anomalous cyclone to the south of the TP hinders warm and humid air flows transportation to the TP, and the anomalous anticyclone to the southeast of Lake Baikal weakens cold air to the south; coupled with weakened convergence and upwards motion, these factors all lead to a decrease in plateau summer monsoonal precipitation.

A deep water shelly fauna from the uppermost Ordovician in northwestern Hunan, South China and its paleoecological implications - Jiayu Rong; Xin Wei; Renbin Zhan; Yi Wang (Science China Earth Sciences, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Effects of simvastatin on the function of splenic CD4+ and CD8+ T cells in sepsis mice - Bingbing Kong; Xiaofeng Wang; Wenping Yang; Xin Zhao; Rong Zhang; Yu Wang (Immunologic Research, 2018)

Genome-wide identification and expression analysis of the B-box gene family in the Apple (Malus domestica Borkh.) genome - Xin Liu; Rong Li; Yaqing Dai; Xuesen Chen; Xiaoyun Wang (Molecular Genetics and Genomics, 2018)

Detrital apatite fission track constraints on Cenozoic tectonic evolution of the northeastern Qinghai-Tibet Plateau, China: Evidence from Cenozoic strata in Lulehe section, Northern Qaidam Basin - Ding-ding Du; Cheng-jun Zhang; Muhammad Saleem Mughal; Xiao-yu Wang; Dembele Blaise; Jun-ping Gao; Yuan Ma; Xin-rong Luo (Journal of Mountain Science, 2018)

A new flavonoid from Sophora flavescens Ait. - Rong Huang; Yi Liu; Lin-Lin Zhao; Xi-xin Chen; Feng Wang; Wei Cai; Lei Chen (Natural Product Research, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Selenium protects against cadmium-induced kidney apoptosis in chickens by activating the PI3K/AKT/Bcl-2 signaling pathway - Rong-kun Bao; Shu-fang Zheng; Xin-yue Wang (Environmental Science and Pollution Research, 2017)

A Review of Geophysical Exploration Technology for Mine Water Disaster in China: Applications and Trends - Tuo Lu; Sheng-dong Liu; Bo Wang; Rong-xin Wu; Xiong-wu Hu (Mine Water and the Environment, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Characterizing the interaction of groundwater and surface water in the karst aquifer of Fangshan, Beijing (China) - Haibo Chu; Jiahua Wei; Rong Wang; Baodong Xin (Hydrogeology Journal, 2017)

Repeated pre-training sleep restriction in adolescent rats impaired spatial performance - Su-Rong Yang; Huan-Xin Sun; Zhen-Zhen Hu; Si-Heng Wang; Hui Sun; Yin-Jia Xue; Chen-Bo Ye (Sleep and Biological Rhythms, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Genome-wide analysis of Gro/Tup1 family corepressors and their responses to hormones and abiotic stresses in maize - Hongyou Li; Kaifeng Huang; Hanmei Du; Hongling Wang; Xin Chen; Shibin Gao; Hailan Liu; Moju Cao; Yanli Lu; Tingzhao Rong; Suzhi Zhang (Journal of Plant Biology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

Preparation of Bacterial Cellulose/Inorganic Gel of Bentonite Composite by In Situ Modification - Bo Wang; Gao-xiang Qi; Chao Huang; Xiao-Yan Yang; Hai-Rong Zhang; Jun Luo; Xue-Fang Chen; Lian Xiong; Xin-De Chen (Indian Journal of Microbiology, 2016)

Eco-toxicological effects of two kinds of lead compounds on forest tree seed in alkaline soil - Nan Yang; Fu-rong Zhou; Jin-xin Wang (Environmental Monitoring and Assessment, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Age-related changes in photosynthesis and water relations of revegetated Caragana korshinskii in the Tengger desert, Northern China - Jing-Ting Bao; Jin Wang; Xin-Rong Li; Zhi-Shan Zhang; Jie-Qiong Su (Trees, 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Interlocking Intramedullary Nails in Fracture Treatment - Xiao Ouyang; Jing Rong Wang; Shi Dong Hong; Feng Xin; Lin Wang; Xiao Wei Yang; Jian Wang (Cell Biochemistry and Biophysics, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Novel Interactive Partners of Neuroligin 3: New Aspects for Pathogenesis of Autism - Chen Shen; Li-rong Huo; Xin-liang Zhao; Pei-rong Wang; Nanbert Zhong (Journal of Molecular Neuroscience, 2015)

MALDI-TOF MS analysis of the extracellular polysaccharides released by the diatom Thalassiosira pseudonana under various nutrient conditions - Xin-Xin Ai; Jun-Rong Liang; Ya-Hui Gao; Samuel Chun-Lap Lo; Fred Wang-Fat Lee; Chang-Ping Chen; Chun-Shan Luo; Chao Du (Journal of Applied Phycology, 2015)

Abundance and distribution of fatty acids in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Journal of Ocean University of China, 2015)

The anti-angiogenic role of discoidin domain receptor 2 (DDR2) in laser-induced choroidal neovascularization - Tong Zhu; Jie Zhu; Xin Bu; Hu Zhao; Shuya Zhang; Yuan Chang; Rong Li; Libo Yao; Yusheng Wang; Jin Su (Journal of Molecular Medicine, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

An improved SCGM(1,m) model for multi-point deformation analysis - Qi-jie Wang; Chang-cheng Wang; Rong-an Xie; Xin-qing Zhang; Jian-jun Zhu (Geosciences Journal, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Exogenous hydrogen peroxide enhanced the thermotolerance of Festuca arundinacea and Lolium perenne by increasing the antioxidative capacity - Yan Wang; Jie Zhang; Jian-Long Li; Xin-Rong Ma (Acta Physiologiae Plantarum, 2014)

Component characteristics of polycyclic aromatic compounds in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Acta Oceanologica Sinica, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Heavy metal and organic contaminants in mangrove ecosystems of China: a review - Zai-Wang Zhang; Xiang-Rong Xu; Yu-Xin Sun; Shen Yu; Yong-Shan Chen; Jia-Xi Peng (Environmental Science and Pollution Research, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Assessing the real value of farmland in China - Rong Hu; Dao-chi Qiu; De-ti Xie; Xin-ya Wang; Lin Zhang (Journal of Mountain Science, 2014)

Diallyl disulfide inhibits proliferation and transdifferentiation of lung fibroblasts through induction of cyclooxygenase and synthesis of prostaglandin E2 - Yanhua Wang; Rong Cao; Bo Wei; Xiaoyu Chai; Dan Sun; Y. Guan; Xin-min Liu (Molecular and Cellular Biochemistry, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Component characteristics of organic matter in hydrothermal barnacle shells from Southwest Indian Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Huijing Zhao; Baoju Yang; Kunbo Rong; Yao Ma (Acta Oceanologica Sinica, 2013)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Gorham-Stout syndrome in mainland China: a case series of 67 patients and review of the literature - Po Hu; Xiang-gui Yuan; Xin-yang Hu; Fa-rong Shen; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Response of leaf, sheath and stem nutrient resorption to 7 years of N addition in freshwater wetland of Northeast China - Rong Mao; Chang-Chun Song; Xin-Hou Zhang; Xian-Wei Wang; Zheng-Hai Zhang (Plant and Soil, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Associations between gene polymorphisms in fatty acid metabolism pathway and preterm delivery in a US urban black population - Xin Liu; Guoying Wang; Xiumei Hong; Hui-Ju Tsai; Rong Liu; Shanchun Zhang; Hongjian Wang; Colleen Pearson; Katherin Ortiz; Deli Wang; Emmet Hirsch; Barry Zuckerman; et al. (Human Genetics, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Silicon-mediated amelioration of zinc toxicity in rice (Oryza sativa L.) seedlings - Hai-Hong Gu; Shu-Shun Zhan; Shi-Zhong Wang; Ye-Tao Tang; Rufus L. Chaney; Xiao-Hang Fang; Xin-De Cai; Rong-Liang Qiu (Plant and Soil, 2012)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Inhibition of Endogenous Hydrogen Sulfide Generation is Associated with Homocysteine-Induced Neurotoxicity: Role of ERK1/2 Activation - Xiao-Qing Tang; Xin-Tian Shen; Yi-E Huang; Rong-Qian Chen; Yan-Kai Ren; Heng-Rong Fang; Yuan-Yuan Zhuang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Seismic analysis of the active character of the Taihang Mountain piedmont fault - Ming-Cai Xu; Jing-Hua Gao; Li-Xin Rong; Guang-Ke Wang; Xiao-Jiang Wang (Applied Geophysics, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Assessment of effects of climate change and grazing activity on grassland yield in the Three Rivers Headwaters Region of Qinghai–Tibet Plateau, China - Jiang-Wen Fan; Quan-Qin Shao; Ji-Yuan Liu; Jun-Bang Wang; Warwick Harris; Zhuo-Qi Chen; Hua-Ping Zhong; Xin-Liang Xu; Rong-Gao Liu (Environmental Monitoring and Assessment, 2010)

Differentiation and distribution of indica and japonica rice varieties along the altitude gradients in Yunnan Province of China as revealed by InDel molecular markers - Zhiyuan Xiong; Shujie Zhang; Yunyue Wang; Brian V. Ford-Lloyd; Min Tu; Xin Jin; Yue Wu; Huanxin Yan; Xiao Yang; Ping Liu; Bao-Rong Lu (Genetic Resources and Crop Evolution, 2010)

Normal Shear Stress and Vascular Smooth Muscle Cells Modulate Migration of Endothelial Cells Through Histone Deacetylase 6 Activation and Tubulin Acetylation - Yan-Hua Wang; Zhi-Qiang Yan; Ying-Xin Qi; Bin-Bin Cheng; Xiao-Dong Wang; Dan Zhao; Bao-Rong Shen; Zong-Lai Jiang (Annals of Biomedical Engineering, 2010)

Curcumin prevents liver fibrosis by inducing apoptosis and suppressing activation of hepatic stellate cells - Jian-Chang Shu; Ya-Jun He; Xia Lv; Guo-Rong Ye; Le-Xin Wang (Journal of Natural Medicines, 2009)

Distribution, biomass, and dynamics of roots in a revegetated stand of Caragana korshinskii in the Tengger Desert, northwestern China - Zhi-Shan Zhang; Xin-Rong Li; Li-Chao Liu; Rong-Liang Jia; Jing-Guang Zhang; Tao Wang (Journal of Plant Research, 2009)

Effects of ginkgolide B on neuronal discharges in paraventricular nucleus of rat hypothalamic slices - Yue Lin; Ru Wang; Xin Wang; Rui-Rong He; Yu-Ming Wu (Neuroscience Bulletin, 2008)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Overexpression of CyclinD1 and underexpression of p16 correlate with lymph node metastases in laryngeal squamous cell carcinoma in Chinese patients - Zhi-jie Fu; Zhi-yong Ma; Qi-rong Wang; Da-peng Lei; Rong Wang; Chun-xi Liu; Xin-liang Pan (Clinical & Experimental Metastasis, 2008)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Changes of Porcine Growth Hormone and Pituitary Nitrogen Monoxide Production as a Response to Cadmium Toxicity - Xin-Yan Han; Qi-Chun Huang; Bo-Jing Liu; Zi-Rong Xu; Yi-Zhen Wang (Biological Trace Element Research, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Evaluation of caspase-dependent apoptosis during fluoride-induced liver lesion in pigs - Xiu An Zhan; Min Wang; Zi Rong Xu; Wei Fen Li; Jian Xin Li (Archives of Toxicology, 2006)

Molecular Cloning and Characterization of a Novel Human C4orf13 Gene, Tentatively a Member of the Sodium Bile Acid Cotransporter Family - Xianqiong Zou; Dianzuo Wang; Guanzhou Qiu; Chaoneng Ji; Feng Jin; Maoqing Wu; Huarui Zheng; Xin Li; Liyun Sun; Yu Wang; Rong Tang; Robert Chunhua Zhao; et al. (Biochemical Genetics, 2005)

Conversion rates of surface HOx radicals in Beijing City - Xin-rong Ren; Li-xin Wang; Hui-xiang Wang; Guo-fang Miao (Chinese Geographical Science, 2004)

Application of geographical parameter database to establishment of unit population database - Chun Dong; Rong Zhao; Ji-ping Liu; Gui-xin Wang; Xi-zhi Wu (Chinese Geographical Science, 2003)